Advanced trends in ICT for innovative business management - Szymczyk, Katarzyna; El Emary, Ibrahiem M. M. (Boca Raton, FL : CRC Press, 2021)
This book contains a collection of scientific chapters addressing the emerging trends in IT and telecommunications, as well as the issues that accompany them in business. It addresses issues in cyber applications, ICT solutions and innovative cyber know-how, and demonstrates how high-tech IT communications resources can be used to improve business production, sales and service strategies, supply chains and logistics. The book is based on articles from ICCMIT'20, extending their approach to specific chapters. The chapters cover issues such as financial management, technological upgrades, Industry 4.0 and the trend towards sustainable development. It utilizes examples of technologically advanced enterprises developing under Industry 4.0 assumptions at the stage of digital transformation, which integrate digital technologies and business processes. In addition, this book discusses issues related to cyber risk management and the implementation of a number of safeguards for digitized enterprises. Enterprises that orient themselves towards technological innovations find that they can reach customers faster, are more effectively managed and can achieve a competitive advantage over other businesses. This book will be a great aid to professionals in such companies, both in IT departments and in the management team.
OCLC-licensed vendor bibliographic record.
Keywords: Industrial management -- Information technology; Business -- Data processing; Business enterprises -- Technological innovations; COMPUTERS / Groupware; TECHNOLOGY / Telecommunications